The Use of Flash Media as an Innovation in Chemistry Learning to Improve Student Learning Achievement in Atomic Structure Material - I Made Krisna Budi; Ni Nyoman Nuryani (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: This study aims to determine the effect of using Flash-based learning media on students’ learning achievement in chemistry, specifically on the topic of atomic structure, compared to conventional teaching methods. Methodology: This study employed a quasi-experimental design using a pretest-posttest control group design. The instrument used was a multiple-choice test consisting of 20 items. Data were collected through pretest and posttest. Data analysis included validity and reliability testing, homogeneity test using F-test, and hypothesis testing using t-test with pooled variance. Main Findings: The results showed that students taught using Flash media achieved higher learning outcomes compared to those taught using conventional methods. The experimental group demonstrated better average scores and higher classical completeness. Statistical analysis indicated a significant difference between both groups, confirming that Flash media positively affects students’ achievement in atomic structure learning. Novelty/Originality of this study: This study introduces the application of specifically designed Flash media for atomic structure learning, integrating interactive animation and conceptual visualization. It provides empirical evidence of its effectiveness, offering a more focused approach compared to previous general multimedia studies and contributing to innovation in chemistry learning media development.